2020
DOI: 10.1186/s12871-020-0943-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of adenosine A1 receptors abolished the nutritional ketosis-evoked delay in the onset of isoflurane-induced anesthesia in Wistar Albino Glaxo Rijswijk rats

Abstract: Background: It has been demonstrated that administration of exogenous ketone supplement ketone salt (KS) and ketone ester (KE) increased blood ketone level and delayed the onset of isoflurane-induced anesthesia in different rodent models, such as Wistar Albino Glaxo Rijswijk (WAG/Rij) rats. The modulatory effect of adenosinergic system may have a role in the ketone supplementation-evoked effects on isoflurane-generated anesthesia. Thus, we investigated whether adenosine receptor antagonists can modulate the ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 74 publications
(165 reference statements)
3
18
0
Order By: Relevance
“…We demonstrated previously that intragastric gavage of not only KE and MCT oil but also KEMCT (mix of KE and MCT oil in a 1:1 ratio; ad libitum access to normal rat chow + 2.5g/kg body weight KEMCT) effectively induced and maintained ketosis without causing side effects ( Ari et al, 2016 ; Kesl et al, 2016 ; Kovács et al, 2020 ). Therefore, in this study, 2.5 g/kg dosage of KEMCT was administered once a month by intragastric gavage for 17 months.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…We demonstrated previously that intragastric gavage of not only KE and MCT oil but also KEMCT (mix of KE and MCT oil in a 1:1 ratio; ad libitum access to normal rat chow + 2.5g/kg body weight KEMCT) effectively induced and maintained ketosis without causing side effects ( Ari et al, 2016 ; Kesl et al, 2016 ; Kovács et al, 2020 ). Therefore, in this study, 2.5 g/kg dosage of KEMCT was administered once a month by intragastric gavage for 17 months.…”
Section: Methodsmentioning
confidence: 98%
“…Similar to our previous studies ( Kovács et al, 2018 , 2020 ), blood was taken from the tail vein of rats about 60 min after the gavage, and βHB and glucose levels were measured by a commercially available glucose and ketone monitoring system (Precision Xtra TM , Abbott Laboratories, Abbott Park, IL, United States). This instrument only measures blood levels of R-βHB.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In both studies, KSMCT treatment significantly elevated the blood level of βHB. In another study, they showed that the same KSMCT supplementation protocol alleviated isoflurane-induced anesthesia (immobility), and this effect was mediated through A 1 R but not A 2 R receptors (109). This observation was further confirmed in yet another study by the same group, where KEKS food [standard chow with mixed in ketone esters and ketone salts (110)] supplementation decreased the lipopolysaccharideinduced elevation of SWD in the same rat model, while A 1 R, but not A 2A R antagonism abolished the anti-seizure effect of KEKS supplementation (111).…”
Section: Differential Effects Of C8 and C10mentioning
confidence: 97%